Clinical research Relationship between codon 249 mutation in exon 7 of p53 gene and diagnosis of hepatocellular carcinoma - Gamal El-Din, Hesham; Ghafar, Nagwa Abdel; Saad, Nevine E.; Aziz, Mona; Rasheed, Dina; Hassan, Eman Mahmoud (Archives of Medical Science, 2010)
Introduction: Hepatocellular carcinoma (HCC) is one of the most common malignancies worldwide. Multiple genetic and epigenetic changes are involved in the molecular pathogenesis of HCC. Heat shock proteins have essential roles in protecting cells from the potentially lethal effects of stress. Among them, HSP70 are often overexpressed in cells of various cancers and have been suggested to contribute to tumourigenesis. p53 mutations in codon 249 have also been identified in HCC. Material and methods: Fifty patients with liver disease were enrolled in this study compared to 10 healthy volunteers. The studied patients were divided into 2 groups: group I includes those suffering from HCC, group II includes those suffering from post-hepatitis B and C liver cirrhosis. The presence of p53 gene mutation was detected by DNA extraction from whole blood of patients and controls followed by polymerase chain reaction then restriction fragment length polymorphism (RFLP) analysis of codon 249 of exon 7. We also studied the genotypes of the HSP70 gene by PCR followed by RFLP analysis. Results: Our results revealed no statistical difference between group I, group II, and the control group as regards exon 7 mutation of the p53 gene. Also the frequency of polymorphic genotypes of HSP70 showed no significant difference between the 3 studied groups. Conclusions: The present study supports the view that the incidence of point mutation of p53 codon 249 mutations in exon 7 of the p53 gene may not play a role in carcinogenesis of HCC in Egyptian patients. Also, genetic polymorphism in HSP70 was not associated with high risk of future development of HCC.